DESAIN LINGKUNGAN BELAJAR INOVATIF BERBASIS DEEP LEARNING UNTUK MENINGKATKAN KETERAMPILAN EKONOMI SISWA SMA NEGERI 11 KOTA TERNATE - Tamaela, Trinola Aindriyany; Zulaeha, Ode; Bunga, Meychin Marta; Ilham, Sintia (Jurnal Pendidikan dan Ekonomi (JUPEK), 2025)
This study aims to design an innovative learning environment based on deep learning to improve students' economic skills at SMA Negeri 11 Ternate City. With an interactive and contextual approach, this study shows that economic learning supported by artificial intelligence technology can improve students' abilities in economic data analysis and financial decision making. The Didactic Design Research (DDR) method was used to design and rotate learning practices. The results of the study showed a significant increase in students' critical thinking skills and understanding of economic concepts, as well as positive changes in students' attitudes towards learning. This innovation in education is expected to answer the challenges of 21st century skills in the era of the industrial revolution 4.0.